2020
DOI: 10.28982/josam.800830
|View full text |Cite
|
Sign up to set email alerts
|

Sexual dysfunction and associated risk factors in multiple sclerosis

Abstract: Sciences on 5/7/2019 with a decision number of 318. All procedures in this study involving human participants were performed in accordance with the 1964 Helsinki Declaration and its later amendments. Etik Kurul Onayı: Çalışma onayı Sağlık Bilimleri Üniversitesi Bakırköy Ruh Sağlığı ve Sinir Hastalıkları Eğitim ve Araştırma Hastanesi Etik Kurulu'ndan 318 sayılı karar ile 07.05.2019 tarihinde alınmıştır. İnsan katılımcıların katıldığı çalışmalardaki tüm prosedürler, 1964 Helsinki Deklarasyonu ve daha sonra yapıl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 20 publications
0
1
0
Order By: Relevance
“…Moreover, in the present study, we found higher age, longer duration of disease, lower educational level, higher EDSS, higher BDI, ASEX, and MMMS scores in patients with SD. Duration of disease and depression have been suggested as important factors associated with SD 26,27 . Koseoglu et al suggested that increasing age was an independent factor for SD, and higher EDSS scores might be related to SD because of concomitant depression 26 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, in the present study, we found higher age, longer duration of disease, lower educational level, higher EDSS, higher BDI, ASEX, and MMMS scores in patients with SD. Duration of disease and depression have been suggested as important factors associated with SD 26,27 . Koseoglu et al suggested that increasing age was an independent factor for SD, and higher EDSS scores might be related to SD because of concomitant depression 26 .…”
Section: Discussionmentioning
confidence: 99%
“…Duration of disease and depression have been suggested as important factors associated with SD 26,27 . Koseoglu et al suggested that increasing age was an independent factor for SD, and higher EDSS scores might be related to SD because of concomitant depression 26 . In agreement with recent studies, we showed that female MS patients had more frequent sexual problems than males 9 .…”
Section: Discussionmentioning
confidence: 99%
“…Multiple sclerosis (MS) is a chronic, autoimmune, demyelinating disease of the central nervous system (CNS) [1]. Although brain stem involvement is common at the onset of MS and during the course of the disease, MS patients rarely have isolated cranial nerve involvement.…”
Section: Introductionmentioning
confidence: 99%